Africa agriculture transformation scorecard performance and lessons for Eswatini - Mndawe, H.; Mbuyisa, H.; Nhlengethwa, Sibusiso; Matchaya, Greenwell C.; Nhemachena, Charles (2019)
The objective of this brief is to analyze Eswatini’s performance and discuss lessons from the implementation of the inaugural CAADP BR mechanism. Based on the results, recommendations are proposed for strengthening mutual accountability and performance of the agriculture sector in Eswatini. The analysis is based on results of the Africa Agriculture Transformation Scorecard (AATS) that was presented to African Heads of State and Government in January 2018. Additional information for the analysis came from technical notes in Eswatini’s BR report. Furthermore, experiences and lessons from continental and regional engagements in the implementation of the BR process were also integrated in the analysis.